Severe Clinical Impact of Multiple Wasp Stings: A Case Report of Acute Kidney Injury - Fauziyah, Hana; Nasution, Bayu Rusfandi; Nasution, Alwi Thamrin (Indonesian Journal of Kidney and Hypertension, 2024)
Wasp stings are prevalent in Indonesia and have occasionally resulted in fatalities. Wasp stings can potentially induce a small localized allergic response, systemic reactions, or even life-threatening illnesses. Receiving several stings from wasps can cause systemic inflammation, resulting in acute kidney injury. We present a case of a 51-year-old female who experienced severe renal impairment as a result of repeated wasp stings. Following the stings, the patient promptly obtained medical attention. However, on the second day after the incident, the patient's renal function declined and experienced anuria. The ultrasonography indicates the presence of nephritis. The patient presented with 103 sting wounds, which resulted in local reactions and were accompanied by systemic symptoms. The patient was administered high-dose steroids and underwent five intermittent hemodialysis sessions, which effectively restored their kidney function. Evidence of enhanced renal function was demonstrated through the restoration of normal urine production, elevated glomerular filtration rate, and significant clinical improvements in the patient. This case illustrates the severe impact on the kidney of a generalized wasp sting and the effect of promptly receiving medical treatment following an enormous wasp sting on the patient's prognosis. Initiating dialysis promptly is crucial for rapidly eliminating toxins and thus preserving renal function.